Translating research evidence into clinical practice: a reminder of important clinical lessons in management of resistant hypertension through a case study in general practice - Yap, Timothy; Affandi, Jacquita; Reid, Christopher; Xu, Daniel (2020)
© BMJ Publishing Group Limited 2020. No commercial re-use. See rights and permissions. Published by BMJ.